2017
DOI: 10.1021/acs.nanolett.7b03414
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Intersubband Photodetection in GaN/AlN Nanowires

Abstract: Intersubband optoelectronic devices rely on transitions between quantum-confined electron levels in semiconductor heterostructures, which enables infrared (IR) photodetection in the 1-30 μm wavelength window with picosecond response times. Incorporating nanowires as active media could enable an independent control over the electrical cross-section of the device and the optical absorption cross-section. Furthermore, the three-dimensional carrier confinement in nanowire heterostructures opens new possibilities t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…27,28 Therefore, the semi-polar growth of GaN/InGaN MQWs is the most preferred and is currently actively studied for GaN-based optical applications in leading laboratories. [29][30][31][32][33][34] In this work, we fabricate the next-generation 3-D semipolar GaN/InGaN hierarchical NWs grown on a Si NWtemplate and characterize their optical properties. The morphology of the Si NWs is controlled with metal-assistedchemical-etching (MACE) together with the morphology of the GaN NWs grown by metal-organic chemical vapor deposition (MOCVD).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Therefore, the semi-polar growth of GaN/InGaN MQWs is the most preferred and is currently actively studied for GaN-based optical applications in leading laboratories. [29][30][31][32][33][34] In this work, we fabricate the next-generation 3-D semipolar GaN/InGaN hierarchical NWs grown on a Si NWtemplate and characterize their optical properties. The morphology of the Si NWs is controlled with metal-assistedchemical-etching (MACE) together with the morphology of the GaN NWs grown by metal-organic chemical vapor deposition (MOCVD).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the photocurrent of GaN NW photodetectors presents a sub-linear dependence on the illumination power [28,[34][35][36][37]. However, Spies et al [38] demonstrated that such devices can behave as linear detectors, depending on the direction of the applied bias and the NW diameter.…”
Section: Review Of Studies Based On Custom Membrane-chipsmentioning
confidence: 99%
“…Using GaN/AlN (2 nm / 3 nm) nanowire heterostructures with ISB absorption around 1.55 µm, a single nanowire QWIP has been demonstrated [189]. The spectral response of the detector was obtained by measuring the photocurrent induced by various laser diodes operating at different wavelengths along the near-IR spectrum, as shown in figure 21.…”
Section: Interband Nanowire Photodetectorsmentioning
confidence: 99%